2012
DOI: 10.1111/2049-632x.12003
|View full text |Cite
|
Sign up to set email alerts
|

Time-course proteomic profile ofCandida albicansduring adaptation to a fetal serum

Abstract: Candida albicans is a commensal organism; however, it causes fatal diseases if the host immunity is compromised. The mortality rate is very high due to the lack of effective treatment, leading to ceaseless demand for novel pharmaceuticals. In this study, time-course proteomics of C. albicans during adaptation to fetal bovine serum (FBS) was described. Time-course proteomics is a promising way to understand the exact process of going adaptation in dynamically changing environments. Candida albicans was cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
(54 reference statements)
2
22
0
Order By: Relevance
“…For instance, a system employing a long monolithic silica capillary column (350 cm) successfully identified 2,602 proteins produced in Escherichia coli cells in a single experiment [14]. Aoki et al [15] applied the LC-MS/ MS system to a time-course proteomic analysis of C. albicans during adaptation to fetal bovine serum (FBS). In this study, C. albicans was first grown in a YPD medium and transferred to a YNB ± FBS medium.…”
Section: Time-course Proteomic Analysis Of C Albicansmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, a system employing a long monolithic silica capillary column (350 cm) successfully identified 2,602 proteins produced in Escherichia coli cells in a single experiment [14]. Aoki et al [15] applied the LC-MS/ MS system to a time-course proteomic analysis of C. albicans during adaptation to fetal bovine serum (FBS). In this study, C. albicans was first grown in a YPD medium and transferred to a YNB ± FBS medium.…”
Section: Time-course Proteomic Analysis Of C Albicansmentioning
confidence: 99%
“…In the next step, prepared peptides derived from proteins identified from C. albicans grown in YNB ± FBS media were subjected to LC-MS/MS measurement using a long monolithic silica capillary column (200 cm) [16], and a lot of proteins were successfully identified. Aoki et al [15] identified 1130, 1012, and 701 proteins from the 0, 60 min cultures in YNB −FBS, and 60 min of YNB +FBS samples. In addition, 1034, 933, and 868 proteins were identified from time-course samples of 10, 20, and 40 min of YNB +FBS, respectively (Table 1).…”
Section: Time-course Proteomic Analysis Of C Albicansmentioning
confidence: 99%
See 3 more Smart Citations